2006
DOI: 10.1118/1.2199988
|View full text |Cite
|
Sign up to set email alerts
|

Wall correction factors, Pwall, for parallel-plate ionization chambers

Abstract: The EGSnrc Monte Carlo user-code CSnrc is used to calculate wall correction factors, Pwall,, for parallel-plate ionization chambers in photon and electron beams. A set of Pwall values, computed at the reference depth in water, is presented for several commonly used parallel-plate chambers. These values differ from the standard assumption of unity used by dosimetry protocols by up to 1.7% for clinical electron beams. Calculations also show that Pwall is strongly dependent on the depth of measurement and can var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 24 publications
6
64
1
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] A recent Monte Carlo study in ion chamber dosimetry has suggested that in electron beams the wall correction factor ͑P wall ͒ for thimble ion chambers changes with depth by 2.5% 12 and for parallel-plate ion chambers it varies by as much as 6%. 13 However, in ion chamber dosimetry it is commonly assumed that the wall correction factors are unity. Since the uncorrected ion chamber measurements agree with diode measurements, this prompts the question: does the diode response, i.e., the diode reading per unit absorbed dose to the water, change with depth in a manner similar to the ion chamber's P wall correction?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11] A recent Monte Carlo study in ion chamber dosimetry has suggested that in electron beams the wall correction factor ͑P wall ͒ for thimble ion chambers changes with depth by 2.5% 12 and for parallel-plate ion chambers it varies by as much as 6%. 13 However, in ion chamber dosimetry it is commonly assumed that the wall correction factors are unity. Since the uncorrected ion chamber measurements agree with diode measurements, this prompts the question: does the diode response, i.e., the diode reading per unit absorbed dose to the water, change with depth in a manner similar to the ion chamber's P wall correction?…”
Section: Introductionmentioning
confidence: 99%
“…CSnrc is very efficient in calculating dose ratios for similar geometries that are commonly encountered in radiation dosimetry. It has been extensively used in ion chamber dosimetry 12,13 and can be applied to many other applications as well. As an additional verification of the code, we have used CSnrc to calculate the energy and beam quality dependence of the response of LiF TLD chips in mega-voltage photon and electron beams.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy between pl w and h pl corrections is based on the fact that the ratio of P wall pl and P wall w correction factors for planeparallel chambers in Eq. ͑9͒ differs from unity, 8,11 and this is discussed in detail in Secs. IV C and IV D.…”
Section: Ivb Fluence Correction Factormentioning
confidence: 99%
“…For well-guarded plane-parallel chambers, such as the one recommended in this report, both [77] and McEwen et al [78]). …”
Section: A46 Limiting Value For the Expected Uncertaintymentioning
confidence: 99%
“…[80] and EGSnrc by Verhaegen et al [76] and Buckley and Rogers [77]) and one semiempirical model (by McEwen et al [78]). All of them predict a similar tendency of p wall values slightly above unity at low electron energies and increasing with decreasing energy.…”
Section: A46 Limiting Value For the Expected Uncertaintymentioning
confidence: 99%